Prospective observational study to evaluate the efficacy and safety of the pollen extract Sérélys® in the management of women with menopausal symptoms - Fait, Tomas; Sailer, Manuela; Regidor, Pedro-Antonio (Gynecological endocrinology, 2019)
Safety concerns or contraindications to the use of hormones have resulted in a rise of the use of herbal medicinal products for the management of menopausal symptoms. The pollen extract Sérélys® represents, due to its ingredients and mode of action, a new and innovative alternative for the management of these symptoms. The aim of the present study was to demonstrate the efficacy and safety of Sérélys®. A prospective, open, observational, and multicentre study was performed on 104 menopausal women. The patients received over 3 months the pollen extract Sérélys® containing the extracts PI82 and GC Fem in a dosage of twice 160 mg extract and 5 mg vitamin E. Using a validated menopausal rating score, the improvement of menopausal symptoms was recorded. A significant decrease of different menopausal symptoms was observed between the starting point of the study and after 12 weeks (p < .0001). Hot flashes were reduced by 48.5%, sleep disturbance by 50.1%, depressive mood by 51.2%, irritability by 47.9%, fatigue by 47.8%, vaginal dryness by 39.63% and muscles and joint pain by 27.4%. The pollen extract Sérélys® reduced significant menopausal symptoms showing a very low side effect profile.
Keywords: Plant Extracts; Humans; Menopause; Phytotherapy; lidé středního věku; vazomotorický systém; fytoterapie; Hot Flashes; Vitamin E; Pollen extract; Female; lidé; Sleep Wake Disorders; menopause; rostlinné extrakty; Vasomotor System; ženské pohlaví; menopauza; Middle Aged; Pollen; návaly; poruchy spánku a bdění; Depression; non-estrogenic activity; pyl; prospektivní studie; deprese; vitamin E; antigeny rostlinné; Antigens, Plant; Prospective Studies